Sensitization to Molecular Components in 104 Atopic Dermatitis Patients in Relation to Subgroups of Patients Suffering from Bronchial Asthma and Allergic Rhinitis - Vaňková, Radka; Čelakovská, Jarmila; Bukač, Josef; Krčmová, Irena; Krejsek, Jan; Andrýs, Ctirad (Acta medica (Hradec Kralove), 2020)
BACKGROUND: Atopic dermatitis (AD) is a chronic inflammatory skin disease. The progression from AD to bronchial asthma (AB) and allergic rhinitis (AR) is called atopic march. The aim of this study was to evaluate the difference in the sensitization to molecular components in patients suffering from AD in relation to subgroups of patients with AR and AB. MATERIAL AND METHODS: The complete dermatological and allergological examinations were performed. Specific IgE antibodies against 112 molecular components were measured with the multiplex ImmnoCAP ISAC test. RESULTS: Altogether 104 atopic dermatitis patients (50 men, 54 women) at the average age 40.1 years were examined. The sensitization to molecular components was confirmed in 93.3% of patients. The sensitization to components of mites, grasses, trees, animals, moulds, and shrimps was significantly more frequent in patients with severe form of AD and the sensitization to components of grasses, trees, and moulds was significantly higher in subgroup of patients with AB. In subgroup of patients suffering from AR the higher occurrence of pollen-derived and pollen-food derived PR-10 proteins, grasses, mites, and animals was observed also. CONCLUSIONS: We have confirmed the significant differences in the sensitization to molecular components in patients suffering from severe form of AD, and in subgroups of patients suffering from AB and AR. These molecular components may play the important role in the consecutive development of different allergy pathologies called atopic march.
Keywords: dospělí; Female; Dermatitis, Atopic; multiplex ISAC testing; Adult; Allergens; ženské pohlaví; lidé; Immunoglobulin E; molecular components; atopická dermatitida; Asthma; stupeň závažnosti nemoci; allergic rhinitis; Male; Rhinitis, Allergic; bronchiální astma; alergická rýma; atopic march; imunoglobulin E; alergeny; mužské pohlaví; Severity of Illness Index; severity of atopic dermatitis; bronchial asthma; Humans